2019
DOI: 10.1002/clen.201900251
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Water Quality of Mamasın Dam, Turkey: Using Water Quality Index Method, Ecological and Health Risk Assessments

Abstract: The water quality of Mamasın Dam, the drinking water source for Aksaray in Turkey, is investigated for assessment of ecological and health risks according to data between December 2015 and November 2016. Water quality index, ecological risk, and health risk assessments are determined to depend on the intensity of occurrence of parameters and seasonal and spatial distributions at different depth ranges. As a result, some ions such as Al, As, B, Ba, Co, F, Mn, Ni, Pb, Se, and Zn were found to be exceeding the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Many researchers conduct their studies regarding dam risk assessment with different methods. For example, reference [18] utilized Water Quality Index Method (WQI) for water quality evaluations and revealed that several ions, such as Al, As, B, Ba, Co, F, Mn, Ni, Pb, Se, and Zn, were discovered to surpass the national regulatory standards' limit values. As a result, the WQI values of the water quality are poor (below 60), although the source is suitable for industrial and agricultural use.…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%
“…Many researchers conduct their studies regarding dam risk assessment with different methods. For example, reference [18] utilized Water Quality Index Method (WQI) for water quality evaluations and revealed that several ions, such as Al, As, B, Ba, Co, F, Mn, Ni, Pb, Se, and Zn, were discovered to surpass the national regulatory standards' limit values. As a result, the WQI values of the water quality are poor (below 60), although the source is suitable for industrial and agricultural use.…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%
“…The use of a feasible and effective method of assessing the quality of drinking water is essential to achieve reliable results and to facilitate informed decision-making. Since the 1960s, when Horton developed the first water quality index (WQI), many methods of assessing water quality have been proposed [13][14][15]. The rapid development of water quality assessment methods improves our understanding of water quality either by a single numeric number or by a more sophisticated interpretation of water quality characteristics [16].…”
Section: Related Workmentioning
confidence: 99%